DISPOSISI POLIGAMI: (Sebuah Telaah Krits Topik Epistemologi Filsafat Ilmu Terhadap Diskursus Poligami) - Khaidarullah (AS-SALAM, 2013)
Disposesi is a genuine treasure of philosophy in Islam was introduced by aMuslim philosopher Baqir as-Sadr. With his pithy thoughts, Baqir bridgingpolar empiricism and rationalism are dichotomous. In the context of theissue of polygamy, with the construction of Disposesi’s think, polygamy isa proposition that is believed to be true in the Qur’an and it is a primaryconception. Furthermore, the conception of the secondary will be representedby both empirical blocks on one side and on the other side of the rationalblock in the interpretation of the text.